(untitled) (Scientific journal of the Fergana State University, 2023)
The article tells about the discovery of the settlement of the Eneolithic and Early Bronze Age in the Fergana Valley by archaeological and anthropological methods and the analysis of the area of its distribution, early agricultural culture and related research, new research results related to "Tashtumor". The morphological structure of soils was also determined using modern methods of field research.